Thermodynamic Analysis of Combined Vapor Compression and Vapor Absorption Refrigeration System - Shaikh, Aamir; Memon, Abdul Ghafoor; Deep, Aakash; Hussain, Tahwer (Mehran University Research Journal of Engineering and Technology; Vol 36 No 3 (2017): July Issue, 2017)
extensively for refrigeration purposes. In this paper, a system is proposed that works using both cycles powered by an IC (Internal Combustion) engine, where mechanical energy is used to run the VC cycle while exhaust gasses are used to operate the VA cycle. The VC cycle works on R12 refrigerant while LiBr-H 2 O combination is selected for operation of VA cycle. Firstly, the refrigeration system is modeled, followed by a parametric study to investigate the impacts of various operating parameters on the system performance. The results exhibit that for maximum chilling and overall performance, the condenser and evaporator pressures in the VC cycle are obtained as 710 and 340 kPa, respectively, whereas generator and absorber temperatures in VA cycle are 85 and 20oC, respectively.